Self-Efficacy, Grit and Perceptions of Rural Employment - Daniel R Terry; Blake Peck; Ed Baker (Rural Nurse Organization; Binghamton University, 2021)
Purpose: General self-efficacy, occupational self-efficacy, and grit have a correlation with academic and practical success amongst nursing students. The role of these same characteristics during the first 18-24 months following the transition from student to nurse is poorly understood. In addition, when a nursing graduate begins to consider a career in a rural area is also remains unclear. This study sought to understand the change, if any, in general self-efficacy, occupational self-efficacy, grit, and rural employment importance that occurred during this transition period. Sample: Nurses after graduating from a three-year Bachelor of Nursing degree (n=28). Method: A follow-up study of a larger longitudinal mixed-methods cohort design used a survey to examine general self-efficacy, occupational self-efficacy, grit, and rural employment importance among novice nurses. Participants had agreed when completing the initial study as students to participate in a follow-up study 18-24-months after graduating. Findings: Occupational self-efficacy increased as the cohort transitioned from student to professional nurse, while grit was remarkably lower between final year students and novice nurses. No change in earlier measures of general self-efficacy or importance placed on rural careers were detected. Conclusions: Following graduation, new clinicians are focused on building professional identity and the development of foundational skills for practice. Clinical agencies have an opportunity to shift the balance between autonomy and support in order to harness these key characteristics in an effort to improve the longevity and progression of nursing graduates within the nursing profession. Keywords: nurses, students, novice, grit, self-efficacy, community apgar DOI: https://doi.org/10.14574/ojrnhc.v21i2.680